Deep Medial Collateral Ligament Tear during Knee Arthroscopy - Nandi, Sumon; Parker, Richard (The Journal of Knee Surgery, 2012)
We report herein deep medial collateral ligament (MCL) tear of the knee with application of valgus stress during arthroscopic partial medial meniscectomy. With symptomatic treatment only, the patient went on to heal this injury without incident and recovered in an expected fashion from arthroscopic surgery. There is no earlier report in the literature of deep MCL tear during knee arthroscopy. Awareness of this entity, its consequences, and optimal management are essential as arthroscopic partial meniscectomy is the most common surgery performed by orthopedic surgeons.
Keywords: medial collateral ligament; deep medial collateral ligament; meniscectomy; arthroscopy; knee